Electronic Effect‐Modulated Enhancements of Proton Conductivity in Porous Organic Polymers. Issue 2 (7th December 2022) - Kim, Sun Young; Kang, Minjung; Kang, Dong Won; Kim, Hyojin; Choe, Jong Hyeak; Yun, Hongryeol; Hong, Chang Seop
Abstract: We proposed a new strategy to maximize the density of acidic groups by modulating the electronic effects of the substituents for high‐performance proton conductors. The conductivity of the sulfonated 1‐MeL40‐S with methyl group corresponds to 2.29×10 −1 S cm −1 at 80 °C and 90 % relative humidity, remarkably an 22100‐fold enhancement over the nonsulfonated 1‐MeL40 . 1‐MeL40‐S maintains long‐term conductivity for one month. We confirm that this synthetic method is generalized to the extended version POPs, 2‐MeL40‐S and 3‐MeL40‐S . In particular, the conductivities of the POPs compete with those of top‐level porous organic conductors. Moreover, the activation energy of the POPs is lower than that of the top‐performing materials. This study demonstrates that systematic alteration of the electronic effects of substituents is a useful route to improve the conductivity and long‐term durability of proton‐conducting materials. Abstract : Porous organic polymers with improved proton conductivity were prepared by modulating substituents with different electronic effects. The sulfonated materials showed top‐tier conductivity, excellent long‐term stability, and low activation energy.